Financial attitude and literacy on financial inclusion: Mediating self-efficacy and moderating subjective norms and social networks in Nepal - Shrestha, Sajeeb Kumar; Thapa, Ganga; Shrestha, Sanket; Pandey, Krishna Prasad; Mahat, Dipak (Edelweiss Applied Science and Technology, 2026)
Financial inclusion is vital for economic empowerment; however, existing studies often emphasize financial literacy and attitudes without exploring the psychological mechanisms and social dynamics that bridge them to inclusion. This study examines the mediating role of self-efficacy in financial attitude, financial literacy, and financial inclusion, alongside the moderating effects of subjective norms and social networks. Using a quantitative research method, data were collected from 399 respondents through a structured questionnaire. SmartPLS was used to test the mediating and moderating effects. Self-efficacy partially mediated the relationship between financial attitude and inclusion and fully mediated the link between financial literacy and inclusion. Financial attitude had a significant direct effect on inclusion, whereas the direct effect of financial literacy was non-significant. Social networks negatively moderated the link between self-efficacy and inclusion, whereas subjective norms showed no moderation. Self-efficacy emerged as the central mechanism driving financial inclusion, with financial literacy influencing inclusion exclusively through self-efficacy. Overreliance on informal social networks may hinder formal financial participation, highlighting the need for confidence-based interventions. This study uniquely integrates psychological and social variables into the financial inclusion framework, demonstrating the exclusive mediating role of self-efficacy for financial literacy and revealing the paradoxical negative influence of social networks on formal inclusion.